Case Report: Specific ABL-Inhibitor Imatinib Is an Effective Targeted Agent as the First Line Therapy to Treat B-Cell Acute Lymphoblastic Leukemia With a Cryptic NUP214::ABL1 Gene Fusion - Egle Stukaite-Ruibiene; Rimvydas Norvilas; Rimvydas Norvilas; Vaidas Dirse; Sigita Stankeviciene; Goda Elizabeta Vaitkeviciene; Goda Elizabeta Vaitkeviciene (Frontiers Media S.A., 2022)
Acute lymphoblastic leukemia (ALL) with recurrent genetic lesions, affecting a series of kinase genes, is associated with unfavorable prognosis, however, it could benefit from treatment with tyrosine kinase inhibitors (TKI). NUP214::ABL1 fusion is detected in 6% of T-cell acute lymphoblastic leukemia (T-ALL), and is very rare in B-ALL. We present a case of adolescent with B-ALL and a cryptic NUP214::ABL1 fusion which was initially missed during diagnostic screening and was detected by additional RNA sequencing. Treatment with specific ABL-inhibitor Imatinib was added later in therapy with a good effect. Initial treatment according to conventional chemotherapy was complicated by severe side effects. At the end of Consolidation, the patient was stratified to a high risk group with allogeneic hematopoietic stem cell transplantation because of insufficient response to therapy. At that time, targeted RNA sequencing detected NUP214::ABL1 gene fusion which was previously missed due to a small microduplication in the 9q34 chromosome region. Gene variant analysis revealed no TKI-resistant ABL1 mutations; therefore, treatment with Imatinib was added to target the NUP214::ABL1 fusion protein. A negative minimal residual disease was achieved, and treatment was downgraded to intermediate risk protocol. Combining routine genetic assays with next-generation sequencing methods could prevent from missing atypical gene alterations. Identification of rare targetable genetic subtypes is of importance in order to introduce targeted therapy as early as possible that may improve survival and reduce toxicity. Treatment with ABL1 inhibitor imatinib mesylate revealed as a highly effective targeted therapy against the leukemia driving protein kinase.